Glomerular Function in Neonates (Iranian Journal of Kidney Diseases, 2012)
Glomerular filtration rate is low in fetal and neonatal life. It increases after birth and reaches approximately 20 mL/min/1.73 m2 at 1 month of age in term and preterm neonates. Various methods have been used to measure glomerular filtration rate in neonates such as inulin clearance, creatinine clearance, and serum cystatin C. Serum creatinine concentrations are influenced by many factors. It is suggested to use other markers which are stable over time and are not affected by muscle mass or tubular reabsorption and secretion. Cystatin C incorporates these characteristics; however, there are some other limitations in the use of cystatin C as a marker of kidney function in neonates. Additionally, the numbers of studies focused on the use of cystatin C in neonates is limited. There is a need for further studies to determine cystatin C's normal range levels and investigate whether cystatin C can replace other tests such as serum creatinine as marker of kidney function in newborn babies. Assessment of newer kidney function tests is also warranted in newborn infants.